Development Of Appropriate Technology Adoption For Coffee Farmers In Sukawangi Village, Sumedang - Bentang Arief Budiman; Hari Purnama; Husna Nugrahapraja; Muhammad Abdur Rasyid; Natas Setiabudhi Daryono Putra; Sri Aswin Suryani; Annisa Ratna Nurillah; Ima Mulyama Zainuddin; Rindia Maharani Putri; Wervyan Shalannanda; Raden Aswin Rahadi (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2019)
In this paper, the authors propose solutions to increase the added value of coffee in the form of the process of making the process of making coffee using appropriate technology adoption. This paper uses qualitative methods of locational survey and literature study. Survey activities are conducted in the form of interviews and observations. The team conducted interviews with coffee farming communities in the area and observed the conditions of coffee farming. The literature study was conducted by synthesizing literature reviews and continued by formulating the theory and principles of appropriate technology in the context of local agriculture in Sukawangi Village, Sumedang Regency, West Java. In this paper, the authors describe the solution proposals related to the problems of coffee farmers in Sukawangi, Sumedang. Two suggestions for increasing the value added of coffee beans are by using appropriate technology adoption. With both of these solutions, it is expected that the quality of coffee plantation in Sumedang can be increased and can be marketed in both domestic and international markets. As a result, the welfare of farmers in Sumedang will increase.